Prevalence and characteristics of mcr-9-positive Salmonella isolated from retail food in China. (15th April 2022) - Sheng, Huanjing; Ma, Jiaqi; Yang, Qiuping; Li, Wei; Zhang, Qian; Feng, Chengqian; Chen, Jin; Qin, Mingqian; Su, Xiumin; Wang, Puyao; Zhang, Jie; Zhou, Wei; et al.
Abstract: The aim of this study was to evaluate prevalence and characteristics of mcr-9 -positive Salmonella isolated from retail food in China. For this purpose, 2486 Salmonella isolated from retail foods from 2007 to 2016 in China were investigated. Based on PCR methods, 5.6% (140/2486) of the isolates were confirmed carrying mcr-9 . Those mcr-9 -positive isolates distributed in 9 of 10 provinces and municipalities and in 8 of 12 food types including poultry-related foods (5.9%, 136/2314) and non-poultry-related foods (2.3%, 4/172). Among 138 Salmonella serotypes, isolates of 8 serotypes were detected carrying mcr-9 . Interestingly, S. Thompson was the most dominant serotype (90.7%, 127/140). Most mcr-9 -positive isolates were susceptible to colistin, but 91.4% of which were multi-drug resistant. Among 140 mcr-9- positive isolates, 116 (82.9%) exhibited extended spectrum β-lactamase (ESBL) producing phenotype, 87.1% of them co-carried bla CTX-M-3 and bla TEM-1 . Significant difference was found between mcr-9- positive isolates recovered before/including 2010 and after 2010, as well as S. Thompson and non- S. Thompson, in terms of detection rate and antibiotic resistance. PFGE revealed close genetic relatedness of mcr-9 -positive ESBL-producing S. Thompson. Our findings indicated that the specificity of transmission of mcr-9 -positive Salmonella in retail foods in China, providing valuable baseline data for food safety risk assessment. Highlights: mcr-9 -positive Salmonella were prevalent in poultry-related foods in China. S. Thompson was the most dominant serotype in mcr-9 -positive Salmonella. Most mcr-9 -positive S. Thompson were susceptible to colistin and polymyxin B, but showed MDR and ESBL phenotype. Close genetic relatedness of mcr-9 -positive S. Thompson was found based on PFGE analysis.